Checklist de Histeridae do sul do Brasil (Insecta: Coleoptera: Staphyliniformia) - Gonçalves, Guilherme Machado; Leivas, Fernando Willyan Trevisan (EntomoBrasilis, 2017)
Resumo. Os Histeridae são besouros predadores, principalmente de larvas de Diptera, que apresentam morfologia diversificada. Ainda há pouca informação sobre os Histerídeos ocorrentes na região Neotropical e no Brasil, com carência principalmente de dados regionais. O presente estudo visa preencher esta lacuna de conhecimento por meio de elaboração uma lista de espécies para a região sul do Brasil. Os dados foram levantados por meio de revisão bibliográfica e complementados com o estudo de exemplares depositados nas principais Coleções Biológica do sul do Brasil. São registrados: 66 gêneros e 157 espécies de Histeridae para a Região sul do país, alocados em 11 tribos e sete subfamílias. Essa é a lista regional mais completa de espécies de Histeridae para o Brasil e a primeira para o sul do país. Checklist of Histeridae from southern Brazil (Insecta: Coleoptera: Staphyliniformia) Abstract. The histerid beetles are predator, mainly larvae Diptera, that present diversified morphology. There is little information about the histerid beetles from Neotropical and Brazil, with a large lack mainly about regional data. Our goal was to present a checklist of Histeridae from southern Brazil in order to fill this gap of knowledge. The data were collected through a bibliographic review and supplemented with the study of specimens deposited in the main Biological Collections from Southern Brazil. There are 66 genera and 157 species of Histeridae for the southern Brazil, allocated in 11 tribes and seven subfamilies. Were recorded: 68 species to State of Paraná, 106 species to State of Santa Catarina and 25 species to State of Rio Grande do Sul. This is the most complete regional checklist of Histeridae species from Brazil and the first to southern of the country.